Внешняя политика Российской Федерации. 1992-1999: учебное пособие (РОССПЭН, 2000)
Экземпляры: аб. (2002) / Инвентарный номер: 44218 / Цена: / Сис.шифр: 66.4(2)я7 / Авт.знак: В 60 / ГРНТИ: 11.25.19 / ББК: 66.4(2)я7